A homologous N/P-codoped carbon strategy to streamline nanostructured MnO/C and carbon toward boosted lithium-ion capacitors. (5th January 2023) - Lei, Da; Hou, Zhidong; Li, Na; Cao, Yunjing; Ren, Lingbo; Liu, Huanyan; Zhang, Yu; Wang, Jian-Gan
Abstract: Lithium-ion capacitors (LICs) are drawing increasingly attention owing to their attractive virtues of high energy/power density and long lifetime. However, overcoming the kinetic mismatch of battery-type anodes and capacitor-type cathodes remains an intractable challenge. In this work, we report a homologous N/P-codoped carbon (NPC) strategy to boost lithium-ion capacitors based on nanostructured MnO/C anodes and carbon cathodes. A controllable phytic acid-assisted polymerization method based on the MnO2 precursors is developed to streamline the fabrication of MnO/NPC core-shell nanowires and NPC nanotubes (NPCT). The NPC is of profound benefit for regulating the surface functionality, porosity, and electron transfer kinetics, which greatly minimizes the kinetic mismatch. The battery-type MnO/NPC anode retains a large capacity of 314 mAh g −1 at a high-rate of 5 A g −1, while the capacitor-type NPCT cathode delivers a 110 mAh g −1 at 0.1 A g −1 . The as-built LICs exhibit a high energy density of 145 Wh kg −1, a high power density of 10 kW kg −1, and good cycling lifespan. The present study will enlighten the significance of N/P dual-doping in designing high-performance LICs. Graphical abstract: Image 1